PELATIHAN PEMBUATAN MINUMAN REMPAH DARI TANAMAN OBAT KELUARGA (TOGA) BAGI IBU-IBU DI KELURAHAN RAWANG SEBAGAI UPAYA MENINGKATKAN EKONOMI KELUARGA - Juwita, Dian Ayu (LPPM Universitas Andalas, 2024)
Herbal plants such as ginger, lemongrass, galangal, and turmeric are commonly grown by residents in their home gardens. These plants have great potential to be processed into traditional beverages. One method of processing is by turning them into herbal or spice drinks. Herbal drinks made from Family Medicinal Plants (TOGA) not only contain active ingredients beneficial to health but also serve as an eco-friendly and economical alternative treatment. This initiative aims to optimize the utilization of TOGA in the community by providing practical training on how to produce and package herbal drinks to enhance their market value, as well as to increase entrepreneurial knowledge among mothers in Kelurahan Rawang. The program adopts a participatory approach, where the community is not merely passive recipients of information but actively involved in the hands-on practice of making herbal drinks. This initiative has successfully enhanced the community’s knowledge and skills in utilizing TOGA to produce healthy and natural herbal drinks. In addition to its health benefits, the activity has also created opportunities for the community to develop small businesses based on local spices. Through this program, it is hoped that the community can become more self-reliant in maintaining family health while also developing the economic potential of TOGA